1871 Miss. Rev. Code 559-60 - (:unkn) unknown (My University, 1871)
ch. 58, art. 13, §§ 2531-35: Every person, who shall challenge another to fight a duel, or who shall send, deliver, or cause to be delivered, any written or verbal messages, purporting or intended to be such challenge, or who shall accept any such challenge or message, or who shall knowingly carry or deliver any such message or challenge, or who shall be present at the time of fighting any duel with deadly weapons, either as second, aid or surgeon, or who shall advise or give assistance to such duel, shall, on conviction thereof, be fined in a sum not less than three hundred dollars, nor exceeding one thousand dollars, or be imprisoned, not less than six months, int eh county jail, or by both such fine and [i]imprisonment. . . . § 2534. If any person shall be guilty of fighting in any village, city, town or other public place, and shall in such fight use any rifle, shot-gun, sword, sword-cane, pistol, dirk, bowie-knife, dirk-knife, or any other deadly weapon, or if any person shall be second or aid in such fight, the person so offending shall be fined not less than three hundred dollars, or shall be imprisoned, not less than three months, or punished by both such fine and imprisonment; and if any person shall be killed in such fight, the person so killing the other, may be prosecuted and convicted as in other cases of murder.
Keywords: DUELING